1991
DOI: 10.1002/ana.410300109
|View full text |Cite
|
Sign up to set email alerts
|

Increased lymphocyte beta‐adrenergic receptor density in progressive multiple sclerosis is specific for the CD8+, CD28− suppressor cell

Abstract: Beta-adrenergic receptor density on T cells from healthy humans is greatest on suppressor cells (CD8+, CD28-) and the effect of catecholamines, secreted by the sympathetic nervous system, predominates on this subset. The sympathetic skin response, a measure of sympathetic nervous system function, is absent in most patients with chronic progressive multiple sclerosis (MS). We measured beta-adrenergic receptor density on suppressor cells, cytotoxic cells, and monocytes from patients with chronic progressive MS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…Similarly, in the MRL-lpr/lpr mouse, a genetic model of the human autoimmune disease systemic lupus erythematosus, noradrenergic innervation and noradrenaline content were reduced in the spleen prior to the onset of observed splenomegaly and remained reduced at all ages examined [49]. In MS patients, increased β-adrenergic receptor density on PBMCs, including lymphocytes, has been well documented [50][51][52][53][54][55]. This increase in β-adrenoreceptor density has been shown to be correlated with the expression of high affinity IL-2 receptors (IL-2R) on PBMCs and disease activity of RRMS.…”
Section: Adrenergic Receptorsmentioning
confidence: 89%
“…Similarly, in the MRL-lpr/lpr mouse, a genetic model of the human autoimmune disease systemic lupus erythematosus, noradrenergic innervation and noradrenaline content were reduced in the spleen prior to the onset of observed splenomegaly and remained reduced at all ages examined [49]. In MS patients, increased β-adrenergic receptor density on PBMCs, including lymphocytes, has been well documented [50][51][52][53][54][55]. This increase in β-adrenoreceptor density has been shown to be correlated with the expression of high affinity IL-2 receptors (IL-2R) on PBMCs and disease activity of RRMS.…”
Section: Adrenergic Receptorsmentioning
confidence: 89%
“…in vitro [13,41], animal [5,14,39], and clinical studies [4]. Autonomic dysfunction may be a feature not only of the disease but also due to any one of several pathogenetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were confirmed by another study showing that B lymphocytes had the greatest number of b-ARs with 12.1 AE 1.8 fmol/10 6 cells, followed by CD8+ T lymphocytes with 3.4 AE 0.4 fmol/10 6 and CD4+ T lymphocytes with 1.2 AE 0.1 fmol/10 6 cells (Karaszewski et al 1990). In another study, the same authors reported 2.8 AE 0.3 fmol/10 6 cells in CD8+CD28-(suppressor) T cells versus 1.4 AE 0.4 fmol/10 6 cells in CD8+CD28+ (cytotoxic) T cells (Karaszewski et al 1991).…”
Section: T and B Lymphocytesmentioning
confidence: 91%